School Assistance for Organizing Student Activities to Develop Interests and Talents Based on Multiple Intelligences - Sumarni Rumfot; Rudolf Kempa; Paul Arjanto; Vando Kristi Makaruku (DEVOTIONIS, 2024)
Modern education increasingly emphasizes the holistic development of students' potential, recognizing the diverse intelligences each individual possesses. Howard Gardner's Multiple Intelligence (MI) theory posits that individuals have distinct intelligences that can be nurtured through tailored educational approaches. At SMA Negeri 3 Seram Bagian Barat, this concept has been adopted to foster students' interests and talents, creating a supportive learning environment that maximizes their potential. Despite the benefits, the implementation of MI-based activities faces challenges such as the lack of systematic programs and adequate facilities, which hinder comprehensive student development. This study employs a mixed-method approach to understand the application of MI concepts in educational settings. Key activities include intensive workshops for teachers, mentoring, program development, facility enhancements, and continuous evaluation and monitoring. The results indicate significant improvements in both academic and non-academic performance among students, increased teacher competence, and a more conducive learning environment. The success of the MI program is attributed to effective educational management practices that prioritize personalized learning, continuous professional development for teachers, strategic infrastructure investments, and robust evaluation mechanisms. These elements collectively contribute to an educational ecosystem that supports holistic student development and continuous improvement in educational practices. The findings underscore the importance of integrating innovative educational strategies with effective management practices to create dynamic and inclusive learning environments that cater to the diverse needs of all students, ultimately leading to better educational outcomes.